2016
DOI: 10.3390/su8060519
|View full text |Cite
|
Sign up to set email alerts
|

Earth Observation for Maritime Spatial Planning: Measuring, Observing and Modeling Marine Environment to Assess Potential Aquaculture Sites

Abstract: Physical, chemical and biological characteristics of seawaters are primary descriptors for understanding environmental patterns and improving maritime spatial planning for potential aquaculture uses. By analyzing these descriptors in spatial and temporal dimensions, it is possible to characterize the potential productivity performances of different locations for specific aquaculture species. We developed a toolbox that, starting from the actual competing uses of the maritime space, aims at: (a) identifying sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Developing a spatial understanding of where conditions are most suitable for the three most commercially important species of mussels, Crassostrea gigas, Mytilus galloprovincialis, and Ostrea edulis, is required before priority areas for aquaculture expansion can be identified. To do so, we followed the methods outlined in existing literature to derive aquaculture suitability scores (Valentini et al 2016;Davaasuren et al 2010;Andersen et al 2013), which we then vetted with national aquaculture experts. This process defines eleven important indicators related to three criteria: environmental quality, optimal mussel growth conditions and socio-economic considerations (Appendix S.3).…”
Section: Aquaculture Suitabilitymentioning
confidence: 99%
“…Developing a spatial understanding of where conditions are most suitable for the three most commercially important species of mussels, Crassostrea gigas, Mytilus galloprovincialis, and Ostrea edulis, is required before priority areas for aquaculture expansion can be identified. To do so, we followed the methods outlined in existing literature to derive aquaculture suitability scores (Valentini et al 2016;Davaasuren et al 2010;Andersen et al 2013), which we then vetted with national aquaculture experts. This process defines eleven important indicators related to three criteria: environmental quality, optimal mussel growth conditions and socio-economic considerations (Appendix S.3).…”
Section: Aquaculture Suitabilitymentioning
confidence: 99%
“…Furthermore, decision-making processes have been applied in MSP in studies dealing with the protection of environment, ecology, biodiversity, coastal, and seabed habitat features [36][37][38][39][40][41][42][43]; marine traffic [44][45][46][47][48][49][50][51][52][53]; planning strategy of anchorage [54]; and site identification and selection [55][56][57][58]. Most of the studies that have had applied decision making for different activities in MSP deal with ecological issues and regulation of traffic within maritime industrial ports, but none of them made a development of the spatial plans related to the construction and economical aspects of anchorages.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This can be coped with the fact that most countries have just started to apply MSP. The application of DS in MSP has been found in papers dealing with the protection of environment, ecology, biodiversity, coastal, and seabed habitat features [19][20][21][22][23][24][25][26], marine traffic [27][28][29][30][31][32][33][34][35][36], anchorage planning strategy [37], and site identification (selection) [38][39][40]. It can be concluded that most of the papers, in which DSS is used in the planning of various activities in MSP, are based on ecological issues, and on the issue of regulating traffic within maritime industrial ports, but not with the development of spatial plans, and especially not with plans related to the construction of anchorages as a civil engineering problem.…”
Section: Literature Reviewmentioning
confidence: 99%